2019
DOI: 10.1007/s11467-019-0885-4
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium and morphological characterizations of Kelvin–Helmholtz instability in compressible flows

Abstract: We investigate the effects of viscosity and heat conduction on the onset and growth of Kelvin-Helmholtz instability (KHI) via an efficient discrete Boltzmann model. Technically, two effective approaches are presented to quantitatively analyze and understand the configurations and kinetic processes. One is to determine the thickness of mixing layers through tracking the distributions and evolutions of the thermodynamic nonequilibrium (TNE) measures; the other is to evaluate the growth rate of KHI from the slope… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 106 publications
0
30
1
Order By: Relevance
“…The whole kinetic (internal) energy becomes only a bit smaller (larger) with the increasing thermal conductivity. It is concluded that both heat conduction and temperature exert slight influences on the formation and evolution of the KHI, which is absolutely different from previous studies [40][41][42][43][44]. It is noteworthy that previous works are based upon physical models suitable for single-component fluids [40][41][42][43][44], while the present research is on the base of our reliable kinetic model for multicomponent mixtures.…”
Section: Kelvin-helmholtz Instabilitycontrasting
confidence: 73%
See 1 more Smart Citation
“…The whole kinetic (internal) energy becomes only a bit smaller (larger) with the increasing thermal conductivity. It is concluded that both heat conduction and temperature exert slight influences on the formation and evolution of the KHI, which is absolutely different from previous studies [40][41][42][43][44]. It is noteworthy that previous works are based upon physical models suitable for single-component fluids [40][41][42][43][44], while the present research is on the base of our reliable kinetic model for multicomponent mixtures.…”
Section: Kelvin-helmholtz Instabilitycontrasting
confidence: 73%
“…As an essential physical mechanism in turbulence and fluids mixing process, the KHI has been studied extensively with experimental [55][56][57], theoretical [40,41,58], and computational [42][43][44][45] methods during the past decades. In this section, we further utilize the DBM to simulate and investigate the compressible KHI with both hydrodynamic and thermodynamic nonequilibriun effects.…”
Section: Kelvin-helmholtz Instabilitymentioning
confidence: 99%
“…From a computational resource perspective, the remarkable merits are brevity of programming, numerical potency, inherent parallelism, and ease treatment of intricate boundary conditions. This kind of method has comprehensive capacities in quite several fields, from phonon transport [13] to approximate incompressible flows [14][15][16][17][18][19][20][21][22][23][24][25], full compressible flows [26][27][28][29][30][31][32][33][34][35][36][37], dendrite growth [38,39] and thermal multiphase flows [40]. Recently, the mesoscopic kinetics method is also becoming increasingly popular in computational mathematics and engineering science for solving certain NPDEs, including Burgers' equations [41,42], Korteweg-de Vries equation [43], Gross-Pitaevskii equation [44], convection-diffusion equation [45][46][47][48][49][50][51], Kuramoto-Sivashinsky equation [52], wave equation [53,54], Dirac equation [55], Poisson equation…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, Gan et al studied the effects of viscosity and heat conduction on the Kelvin–Helmholtz (KH) instability through the DBM. The authors found the viscosity effects stabilize the KH instability and enhance both the local and global TNE intensities [ 69 ]. Lin et al employed the DBM to investigate the KH instability and found the relaxation time always strengthens the global non-equilibrium, entropy of mixing, and free enthalpy of mixing [ 70 ].…”
Section: Introductionmentioning
confidence: 99%